2008
DOI: 10.1182/blood-2007-09-107953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donor T-cell trafficking and priming site on graft-versus-host disease induction by naive and memory phenotype CD4 T cells

Abstract: Graft-versus-host disease (GVHD) remains a major cause of morbidity and mortality in allogeneic stem cell transplantation. Effector memory T cells (T(EM)) do not cause GVHD but engraft and mount immune responses, including graft-versus-tumor effects. One potential explanation for the inability of T(EM) to cause GVHD is that T(EM) lack CD62L and CCR7, which are instrumental in directing naive T cells (T(N)) to lymph nodes (LN) and Peyer patches (PP), putative sites of GVHD initiation. Thus T(EM) should be relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 55 publications
3
69
0
Order By: Relevance
“…16,17 In contrast, other studies suggested that knockout of b7 was insufficient to modify intestinal GVHD, 18 and that blocking entry to specific secondary lymphoid organs (either peripheral lymph nodes or Peyer's patches) had no effect on GVHD, suggesting redundancy in secondary lymphoid tissue compartments. 19,20 Drawing general conclusions from these individual studies is difficult because of differences in the immunology of GVHD specific to the individual mouse models of HCT used in each of these separate studies. The evidence does support the theory that acute GVHD is initiated by allogeneic activation in secondary lymphoid tissue, with the induction of a specific trafficking phenotype dependent on the location of the secondary lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In contrast, other studies suggested that knockout of b7 was insufficient to modify intestinal GVHD, 18 and that blocking entry to specific secondary lymphoid organs (either peripheral lymph nodes or Peyer's patches) had no effect on GVHD, suggesting redundancy in secondary lymphoid tissue compartments. 19,20 Drawing general conclusions from these individual studies is difficult because of differences in the immunology of GVHD specific to the individual mouse models of HCT used in each of these separate studies. The evidence does support the theory that acute GVHD is initiated by allogeneic activation in secondary lymphoid tissue, with the induction of a specific trafficking phenotype dependent on the location of the secondary lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect is termed "graftversus-leukemia" (GVL). The relative contributions of memory T cells to GVHD and GVL were discussed elsewhere (1). However, the effect is not specific to malignant cells, and simultaneous damage and destruction of healthy cells and tissues via the same or similar mechanisms give rise to GVHD.…”
Section: Andrea S Henden and Geoffrey R Hillmentioning
confidence: 99%
“…61 However, although the secondary lymphoid organs are the likely location for the interaction of APCs and T cells, they are not obligatory for the development of GVHD. 62 Mediators of GVHD Donor T cells are the critical mediators of acute GVHD regardless of the type of antigen severity (Figure 2). Evidence suggests that alloreactive donor T cells consist of several subsets with different stimuli responsiveness, activation thresholds and effector functions.…”
Section: Sensors Of Gvhdmentioning
confidence: 99%